The Influence of Role Ambiguity and Role Conflict on Employee Creativity at PT XYZ - Tinjung Desy Nursanti; Juliano Satria Indra Putra (Indonesia Banking School, 2017)
The objectives of this research are to determine the influence of role ambiguity and role conflict on employee creativity either partially or simultaneously. This research used associative method by collecting primary and secondary data obtained through the literature study, interviews, and distributing questionnaires to 30 respondents that happens to be the employee of PT XYZ. Then data is processed using multiple regression method. From the data analysis, it is shown that role ambiguity has a positive and significant influence to employee creativity as much as 36,9%. Another result of this research shows that role conflict doesn’t have a significant influence on employee creativity with a value of 7,6%. While another result of this research shows that role ambiguity and role conflict simultaneously had positive influence significantly as much as 40,4% on employee creativity at PT XYZ